K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 6 2019

\(3\sqrt{x}=15\)

\(\Leftrightarrow\sqrt{x}=5\)

\(\Leftrightarrow x=5^2\)

\(\Leftrightarrow x=25\)

Vậy x = 25

\(3\sqrt{x}=15\)

\(\Leftrightarrow\sqrt{x}=5\)

\(\Leftrightarrow x=5^2\)

\(\Leftrightarrow x=25\)

\(k\)\(nha\)

1 tháng 8 2018

1/

Ta có:  \(\left(1+\sqrt{15}\right)^2\)= 1 + 15 + \(2\sqrt{15}\)= 16 + \(2\sqrt{15}\)

              \(\sqrt{24}^2\)= 24 = 16 + 8

Vì:     \(\sqrt{15}^2\)= 15 < 16 =\(4^2\)

Nên:   \(\sqrt{15}< 4\)

=>       \(2\sqrt{15}< 8\)

=>       \(16+2\sqrt{15}< 24\)

=>      \(\left(1+\sqrt{15}\right)^2< \sqrt{24}^2\)

Vậy     \(1+\sqrt{15}< \sqrt{24}\)

2/

b/    \(3x-7\sqrt{x}=20\)\(\left(x\ge0\right)\)

<=> \(3x-7\sqrt{x}-20=0\)

<=> \(3x-12\sqrt{x}+5\sqrt{x}-20=0\)

<=> \(3\sqrt{x}\left(\sqrt{x}-4\right)+5\left(\sqrt{x}-4\right)=0\)

<=> \(\left(\sqrt{x}-4\right)\left(3\sqrt{x}+5\right)=0\)

<=> \(\sqrt{x}-4=0\)hoặc \(3\sqrt{x}+5=0\)

<=>   \(\sqrt{x}=4\)hoặc \(3\sqrt{x}=-5\)(vô nghiệm)

<=>   \(x=16\)

Vậy S=\(\left\{16\right\}\)

c/    \(1+\sqrt{3x}>3\)

<=> \(\sqrt{3x}>2\)

<=>   \(3x>4\)

<=>  \(x>\frac{4}{3}\)

d/      \(x^2-x\sqrt{x}-5x-\sqrt{x}-6=0\)(\(x\ge0\))

<=>   \(\left(x^2-5x-6\right)-\left(x\sqrt{x}+\sqrt{x}\right)=0\)

<=>   \(\left(x^2-6x+x-6\right)-\left(x\sqrt{x}+\sqrt{x}\right)=0\)

<=>    \([x\left(x-6\right)+\left(x-6\right)]-\sqrt{x}\left(x+1\right)=0\)

<=>   \(\left(x-6\right)\left(x+1\right)-\sqrt{x}\left(x+1\right)=0\)

<=>   \(\left(x+1\right)\left(x-6-\sqrt{x}\right)=0\)

<=>    \(\left(x+1\right)\left(x-3\sqrt{x}+2\sqrt{x}-6\right)=0\) 

<=>    \(\left(x+1\right)[\sqrt{x}\left(\sqrt{x}-3\right)+2\left(\sqrt{x}-3\right)]=0\)

<=>    \(\left(x+1\right)\left(\sqrt{x}-3\right)\left(\sqrt{x}+2\right)=0\)

<=>     \(x+1=0\)  hoặc \(\sqrt{x}-3=0\)hoặc \(\sqrt{x}+2=0\)

<=>     \(x=-1\)(loại)  hoặc \(x=9\)hoặc \(\sqrt{x}=-2\)(vô nghiệm)

Vậy S={  9 }

9 tháng 8 2018

Mình cần gấp nha mn 😭😭 

22 tháng 7 2020

1) Ta có: \(\frac{x+6\sqrt{x}+9}{x-9}=\frac{\left(\sqrt{x}+3\right)^2}{\left(\sqrt{x}-3\right)\left(\sqrt{x}+3\right)}=\frac{\sqrt{x}+3}{\sqrt{x}-3}\)

15 tháng 8 2017

432 cm

15 tháng 8 2017

432 cm nha

2 tháng 8 2016

\(y-3=\left(15-x\right)-3=12-x\)

\(B=\sqrt{x-4}+\sqrt{12-x}\)

\(B^2=x-4+12-x+2\sqrt{x-4}\sqrt{12-x}\)

\(=8+2\sqrt{\left(x-4\right)\left(12-x\right)}\ge8\)

\(\Rightarrow B\ge\sqrt{8}\)

Dấu bằng xảy ra khi \(\sqrt{\left(x-4\right)\left(12-x\right)}=0\Leftrightarrow\orbr{\begin{cases}x=4\\x=12\end{cases}}\)